Piosenki w pedagogice „łejerskiej” Jerzego Hamerskiego i Elżbiety Drygas (analiza wybranych śpiewników) - Sadowska, Katarzyna (Studia Edukacyjne, 2024)
Despite the recognition by researchers of the importance of universal music education, the crisis in Polish schools has been evident for decades. However, this crisis does not concern the Poznań Primary School No. 83, unique in Poland; its founders, Jerzy Hamerski and Elżbieta Drygas, emphasize that education through art is one of the core assumptions. Since the song is a permanent element of Jerzy Hamerski’s “Łejery” pedagogy and has accompanied his pupils for 50 years, this study focuses on showing the artistic and educational values of selected “Łejery” songs. Two of the six published “Łejery” songbooks were analyzed, i.e. a school songbook titled “When the Bell Rings” and a songbook dedicated to the memory of Emilia Waśniowska. The selection of songbooks is deliberate because the songs contained in them have been the core of the school artistic repertoire of Primary School No. 83 in Poznań for many years. To achieve the goal, the method of source analysis was used, including the method of music analysis. The author analyzed the musical notation (mainly in the area of key, rhythm, melody, and the expressive possibilities of a school-age child), song texts, methodological comments and musical recordings included in the described publications. “Łejery” songs are perfect both in terms of music and literature. All of them are set in an ambience suitable for the performance capabilities of school-age children, all of them have excellent musical arrangement and excellent instrumentation, and the lyrics of each of the pieces focus on matters close to and important to the child.